Carfilzomib or bortezomib in combination with lenalidomide and dexamethasone for patients with newly diagnosed multiple myeloma without intention for immediate autologous stem-cell transplantation (ENDURANCE): a multicentre, open-label, phase 3, randomised, controlled trial. Issue 10 (October 2020) - Kumar, Shaji K; Jacobus, Susanna J; Cohen, Adam D; Weiss, Matthias; Callander, Natalie; Singh, Avina K; Parker, Terri L; Menter, Alexander; Yang, Xuezhong; Parsons, Benjamin; Kumar, Pankaj; Kapoor, Prashant; et al.
Summary: Background: Bortezomib, lenalidomide, and dexamethasone (VRd) is a standard therapy for newly diagnosed multiple myeloma. Carfilzomib, a next-generation proteasome inhibitor, in combination with lenalidomide and dexamethasone (KRd), has shown promising efficacy in phase 2 trials and might improve outcomes compared with VRd. We aimed to assess whether the KRd regimen is superior to the VRd regimen in the treatment of newly diagnosed multiple myeloma in patients who were not being considered for immediate autologous stem-cell transplantation (ASCT). Methods: In this multicentre, open-label, phase 3, randomised controlled trial (the ENDURANCE trial; E1A11), we recruited patients aged 18 years or older with newly diagnosed multiple myeloma who were ineligible for, or did not intend to have, immediate ASCT. Participants were recruited from 272 community oncology practices or academic medical centres in the USA. Key inclusion criteria were the absence of high-risk multiple myeloma and an Eastern Cooperative Oncology Group performance status of 0–2. Enrolled patients were randomly assigned (1:1) centrally by use of permuted blocks to receive induction therapy with either the VRd regimen or the KRd regimen for 36 weeks. Patients who completed induction therapy were then randomly assigned (1:1) a second time to either indefinite maintenance or 2 years of maintenance with lenalidomide. Randomisation was stratified by intent for ASCT at disease progression for the first randomisation and by the induction therapy received for the second randomisation. Allocation was not masked to investigators or patients. For 12 cycles of 3 weeks, patients in the VRd group received 1·3 mg/m 2 of bortezomib subcutaneously or intravenously on days 1, 4, 8, and 11 of cycles 1–8, and day 1 and day 8 of cycles nine to twelve, 25 mg of oral lenalidomide on days 1–14, and 20 mg of oral dexamethasone on days 1, 2, 4, 5, 8, 9, 11, and 12. For nine cycles of 4 weeks, patients in the KRd group received 36 mg/m 2 of intravenous carfilzomib on days 1, 2, 8, 9, 15, and 16, 25 mg of oral lenalidomide on days 1–21, and 40 mg of oral dexamethasone on days 1, 8, 15, and 22. The coprimary endpoints were progression-free survival in the induction phase, and overall survival in the maintenance phase. The primary analysis was done in the intention-to-treat population and safety was assessed in patients who received at least one dose of their assigned treatment. The trial is registered with ClinicalTrials.gov, NCT01863550 . Study recruitment is complete, and follow-up of the maintenance phase is ongoing. Findings: Between Dec 6, 2013, and Feb 6, 2019, 1087 patients were enrolled and randomly assigned to either the VRd regimen (n=542) or the KRd regimen (n=545). At a median follow-up of 9 months (IQR 5–23), at a second planned interim analysis, the median progression-free survival was 34·6 months (95% CI 28·8–37·8) in the KRd group and 34·4 months (30·1–not estimable) in the VRd group (hazard ratio [HR] 1·04, 95% CI 0·83–1·31; p=0·74). Median overall survival has not been reached in either group. The most common grade 3–4 treatment-related non-haematological adverse events included fatigue (34 [6%] of 527 patients in the VRd group vs 29 [6%] of 526 in the KRd group), hyperglycaemia (23 [4%] vs 34 [6%]), diarrhoea (23 [5%] vs 16 [3%]), peripheral neuropathy (44 [8%] vs four [<1%]), dyspnoea (nine [2%] vs 38 [7%]), and thromboembolic events (11 [2%] vs 26 [5%]). Treatment-related deaths occurred in two patients (<1%) in the VRd group (one cardiotoxicity and one secondary cancer) and 11 (2%) in the KRd group (four cardiotoxicity, two acute kidney failure, one liver toxicity, two respiratory failure, one thromboembolic event, and one sudden death). Interpretation: The KRd regimen did not improve progression-free survival compared with the VRd regimen in patients with newly diagnosed multiple myeloma, and had more toxicity. The VRd triplet regimen remains the standard of care for induction therapy for patients with standard-risk and intermediate-risk newly diagnosed multiple myeloma, and is a suitable treatment backbone for the development of combinations of four drugs. Funding: US National Institutes of Health, National Cancer Institute, and Amgen.